Subject Discipline Dimensions of Ict and Learning: History, A Case Study. Issue 1 (1st December 2001) - Haydn, Terry
The paper examines the views of history teachers in the United Kingdom on the potential of new technology for enhancing teaching and learning in history, including their views on which new technology applications are most helpful to teachers of history, what factors are most influential in limiting their use of new technology, and what forms of investment in the use of new technology they regard as most useful. These views are set in the context of considerable enthusiasm and financial investment in new technology on the part of politicians and policy makers, and research evidence which suggests that there is a 'rhetoric-reality' gap between the claims made for the use of new technology in education, and what is current practice. The paper suggests that at least some aspects of the use or non-use of ICT are related to the nature of the subject discipline involved, and that there is a need to take into account subject discipline issues rather than treating new technology as an undifferentiated 'generic' learning tool if the rhetoric-reality gap is to be addressed.